Optimization of Lecturer Resource Management at the Faculty of Islamic Studies - Siahaan, Amiruddin; Nasution, Muhammad Amri; Rafida, Tien; Suryadi, Agus (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study examines Human Resource Management (HRM) practices within the Faculty of Islamic Studies at two universities: Pancabudi Development University and Dharmawangsa University. The research aims to analyze key HRM aspects, including recruitment, selection, competency enhancement, performance management, coaching, and the development of educational staff and faculty members at these institutions. The study adopts a multi-site approach, encompassing both faculties, and utilizes qualitative research methods, specifically a naturalistic interactive approach that involves organic interactions between researchers and participants. The findings reveal that both universities follow general standards for recruitment and selection, such as assessing prior needs and consulting with WR1, although the selection methods varied between institutions. Performance improvement strategies at both universities include participation in various training activities and seminars. Coaching and development efforts at Pancabudi Development University emphasize on-the-job and in-service training, whereas Dharmawangsa University incorporates third-party providers for training initiatives. Moreover, at Pancabudi Development University, the development of educator professionalism is integrated into the broader campus development strategy, while Dharmawangsa University prioritizes ongoing professional development. In conclusion, although the HRM approaches at both universities differ, they are aligned in their overall objectives to enhance HRM and campus development. These findings suggest that institutions implementing well-planned organizational strategies are likely to achieve superior accreditation outcomes.